2017
DOI: 10.1091/mbc.e16-10-0732
|View full text |Cite
|
Sign up to set email alerts
|

The novel mitochondrial matrix protease Ste23 is required for efficient presequence degradation and processing

Abstract: Ste23 is a novel mitochondrial protease located in the matrix. Ste23 degrades presequence peptides derived from imported preproteins. Impaired peptide degradation leads to inhibited presequence-processing machinery and accumulation of immature preproteins. Thus efficient peptide turnover is crucial for mitochondrial proteostasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 36 publications
0
27
0
Order By: Relevance
“…Interestingly, another study analysed peptides released from yeast mitochondria and revealed that the vast majority of released species were free amino acids, followed by peptides composed of up to six amino acids [56]. Peptides longer than six amino acids were released only to a much smaller extent reflecting most likely the concerted action of matrix peptidases [2,8,54,57]. Consistent with this, peptides longer than six amino acids only increased upon deletion of the main matrix peptidase Cym1 [56].…”
Section: The Question Of the Signalmentioning
confidence: 80%
“…Interestingly, another study analysed peptides released from yeast mitochondria and revealed that the vast majority of released species were free amino acids, followed by peptides composed of up to six amino acids [56]. Peptides longer than six amino acids were released only to a much smaller extent reflecting most likely the concerted action of matrix peptidases [2,8,54,57]. Consistent with this, peptides longer than six amino acids only increased upon deletion of the main matrix peptidase Cym1 [56].…”
Section: The Question Of the Signalmentioning
confidence: 80%
“…To assess if lack of PreP results in hampered peptide clearance in mitochondria, we analyzed presequence peptide degradation in soluble mitochondrial extracts [21,29]. For this, isolated mitochondria from control and PreP −/− cells were solubilized in digitonin followed by separation of soluble and membrane fractions via centrifugation [21,29]. Authentic presequence peptides of the dually processed MPP substrate Frataxin (FXN 1−41 and FXN 42−80 ) or presequence peptides of mitochondrial malate dehydrogenase (MDH2 1−19 ) were added to the soluble extract, incubated for different time points and peptide degradation monitored on Nu‐PAGE.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, Am16706 also shows homology to a putative metallopeptidase Ste23p, which processes fungal a-factor mating pheromone [ 59 , 60 ]. Recently, this protein has been shown to work in concert with Cym1 in yeast, to clear N-terminal presequence peptides from the mitochondria [ 61 ], an activity shared by Am3212. Therefore, Am3212 peptidase expression may have been induced to counteract the reduction in levels of Am16706.…”
Section: Discussionmentioning
confidence: 99%